Andrographis paniculata and Orthosiphon stamineus as feed supplement in goats - Roslan, Nurdiyana 'Aqilah; Samsudin, Anjas Asmara @ Ab Hadi; Yaakub, Halimatun; Jusoh, Shokri; Alimon, Abdul Razak (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
The world’s population of ruminants is estimated to produce around 15% of total methane emissions. Besides, the loss of gross energy intake ranging from 2-15% during the methane production of anaerobic fermentation has lead to the reduction of potential conversion of feed energy to metabolizable energy. There are many efforts being made to reduce the metabolizable energy loss which includes the inhibition or reduction of methane production. The methanogenic bacteria in the rumen have a close association with protozoa where methanogens will further utilized the hydrogen that was produced by protozoa for methane formation. Thus, with the reduction in the number of protozoa and methanogens, with the help from fibre-degrading bacteria, formation of methane can be reduced and subsequently reducing the green house effect. Moreover, the use of antibiotics in animals feed has been banned worldwide due to health concern to human being. Previous studies have shown that the addition of herbs in goat’s diet had reduced the microbial population in goats with the supplementation of herbs. Therefore, the project is implemented to help farmers solving these problems to ensure that farmers can produce healthy animals.